Traumatic Diaphragmatic Hernia. A Case Report - Daniel Olivera Fajardo; Jorge Luis Estepa Pérez; Tahiluma Santana Pedraza; Moisés Carillo Pérez (Medisur)
Diaphragmatic trauma is secondary to penetrating injuries and blunt abdominal and thoracic trauma. Traumatic diaphragmatic hernia is an uncommon entity. Its diagnosis poses a real challenge to internists, surgeons and radiologists since it requires a high level of suspicion and appropriate use of diagnostic imaging. Surgical treatment is always needed. For these reasons, we present the case of a patient operated on due to a stab wound to the chest who was subsequently diagnosed with a traumatic diaphragmatic hernia on the left side of the chest. He underwent surgery again and had a successful postoperative recovery.